Zina dalam Al-Quran Analisis Hermeneutika Muhammad Syahrur - Rahmad Akbar; Nurfadhilah Syam; Askahar Askahar (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The issue of zina (fornication/adultery) is one of the most critical topics in Islamic legal studies due to its profound impact on morality, social order, and legal norms. Traditionally, classical exegesis defines zina narrowly as sexual intercourse outside a valid marriage, with strict hudūd punishments: one hundred lashes for unmarried offenders (ghayru muḥṣan) and stoning (rajam) for married offenders (muḥṣan). However, such interpretations are often considered rigidly legal-formal and less attentive to broader humanitarian values. This study aims to analyze the concept of zina in the Qur’an through the lens of Muhammad Shahrur’s hermeneutics of limits (ḥudūd). The research applies a qualitative method using library research, focusing on textual analysis of Qur’anic verses, classical commentaries, and Shahrur’s works. Content analysis was employed to examine the meanings, arguments, and legal implications of Shahrur’s interpretation. The findings reveal that Shahrur rejects the application of stoning (rajam) due to its lack of explicit Qur’anic basis and argues that the maximum punishment for zina is one hundred lashes as stated in QS. An-Nur [24]: 2. He also opens the possibility of minimum sanctions in the form of social or educational measures depending on the socio-historical context. Furthermore, Shahrur redefines zina beyond mere biological acts, extending it to include sexual exploitation, coercion, and violence against women, thus emphasizing the protection of human dignity. In conclusion, Shahrur’s hermeneutics of limits contributes significantly to the reformulation of Islamic criminal law in a more contextual, humanistic, and justice-oriented direction. His approach paves the way for rejecting stoning as a punishment and adopting modern evidentiary mechanisms, thereby offering a contemporary framework for addressing zina within Islamic jurisprudence.